Assessing Students’ Readiness for Online Learning during the COVID-19 Pandemic - Kadex Nugrah Dwi Purwani; Rizqi Claudia Wardani. H (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2022)
The COVID-19 pandemic brought significant changes to the education system, forcing schools to transition from face-to-face learning to online instruction. This sudden shift required students to adapt to a new learning environment that depends heavily on digital literacy, self-regulation, and motivation. This study aimed to assess the level of students’ readiness for online learning during the COVID-19 pandemic at a junior high school in Aimas District. Using a quantitative descriptive design, the research involved 30 eighth-grade students who participated in online learning activities during the pandemic. Data were collected through a questionnaire focusing on key indicators of readiness, including self-directed learning, learner control, motivation, computer and internet self-efficacy, and online communication. The data were analyzed using descriptive statistics to determine the overall readiness level. The results showed that the students’ overall readiness for online learning was at a moderate level. The highest score was found in the motivation aspect, indicating that most students had a positive attitude toward online learning. However, the lowest scores were observed in computer self-efficacy and online communication, suggesting that technical limitations and lack of interaction hindered students’ participation. These findings highlight the need for schools to strengthen digital skills training, provide adequate learning support, and develop strategies that promote active engagement in online environments.